Characteristics of naturally woven Waru bark fiber for eco-friendly composite reinforcement - Wirawan, Willy Artha; Wulansari, Ajeng; Sabitah, Ayan; Putra, Muhammad Rezki Fitri; Gapsari, Femiana; Sartika, Dewi; Ilyas, R.A.; Sapuan, S.M. (Elsevier B.V., 2025)
The aim of this study was to investigate the potential of Waru bark fiber (WBF) as a reinforcement material for composites. To achieve this aim, WBF was extracted using a conventional process, to ensure its purity, and then characterized for physical, mechanical, chemical, and thermal properties. Microstructure analysis was performed using Scanning Electron Microscope (SEM) to show uniform and exceptional fiber sheets with naturally woven fiber shapes. A high value of 152.77 MPa was found for fiber's tensile strength in the mechanical test. Following this discussion, the fiber's crystallinity index (CI) was 56.54 %, and the X-Ray Fluorescence (XRF) test showed a composition ratio of O = 48.63 % and C = 36.74 %. Thermal analysis using Differential Thermal Analysis-Thermogravimetric Analysis (DTA-TGA) showed that the cellulose fiber could withstand temperatures stability up to 312 °C. Finally, this study offered a sustainable solution to reduce the reliance on synthetic fiber in various industries by suggesting the use of reliable WBF as reinforcement.